Florida Solid and Hazardous Waste Regulation Handbook: Occupational Safety and Health Act (OSHA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
Congress passed the Occupational Safety and Health Act to assure that the workplace environment is safe and healthy. To fulfill this purpose, OSHA authorized the Secretary of Labor, who is the head of the Occupational Safety and Health Administration, to set and enforce safety standards for employees working in dangerous circumstances such as handling hazardous wastes. This is EDIS document FE447, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.